Recent trends in rural Geography studies. Theoretical developments and research areas in Latin America - Héctor Ávila Sánchez (Investigaciones Geográficas, 2015)
In this paper it is made a tour through the various theoretical and methodological routes that support the Rural Geography, in its current forms. The article is part of a wider investigation into the trends and state of the art of rurality between the years 1990 and 2010, with emphasis on rural geography perspective and particularly on the contributions that establish French geography and Anglo-Saxon geography. It highlights how these influences have transcended national geographical schools in some countries of Latin America. At the beginning of the discipline in the early twentieth century, emphasizing the identification and description of landscapes, influenced by the importance of regionalist discourse. Subsequently, rural geographical studies developed under the influence of economic geography, mainly describing large areas of agricultural specialization worldwide (cereal production areas, or Mediterranean agriculture, etc.). Later, from the decade of the eighties, analyze the depth of the territorial changes that occur in rural areas, due to changes in the Fordist and post-Fordist production paradigm, and the arrangements resulting from globalization.